2020
DOI: 10.3390/genes11010110
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relevance of DNA Methylation Changes in Immune Differentiation and Disease

Abstract: Immune cells are one of the most complex and diverse systems in the human organism. Such diversity implies an intricate network of different cell types and interactions that are dependently interconnected. The processes by which different cell types differentiate from progenitors, mature, and finally exert their function requires an orchestrated succession of molecular processes that determine cell phenotype and function. The acquisition of these phenotypes is highly dependent on the establishment of unique ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 174 publications
(183 reference statements)
1
53
0
1
Order By: Relevance
“…DNA methylation is a biochemical process involving the addition of a methyl moiety to a cytosine or adenine residue at repeated CpG dinucleotides (CpG island) in gene promoter regions for repressing gene expression, which is part of the epigenetic regulation process of gene expression (Table 3) [63][64][65][66][67][68][69][70][71][72][73][74]. The biochemical process is mediated by DNA methyl-transferase (DNMT) 1, 3a, and 3b.…”
Section: Dna Hypomethylation In Sle-cd4 + T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is a biochemical process involving the addition of a methyl moiety to a cytosine or adenine residue at repeated CpG dinucleotides (CpG island) in gene promoter regions for repressing gene expression, which is part of the epigenetic regulation process of gene expression (Table 3) [63][64][65][66][67][68][69][70][71][72][73][74]. The biochemical process is mediated by DNA methyl-transferase (DNMT) 1, 3a, and 3b.…”
Section: Dna Hypomethylation In Sle-cd4 + T Cellsmentioning
confidence: 99%
“…Coit et al [64] have even reported that CG10152449 in CHST 12 hypomethylation in CD4 + T cells has a very high specificity (64.3%) to the patients with lupus nephritis. De la Calle-Fabregat [70] concluded that DNA methylation is essential for immune differentiation, and its derangement is highly implicated in the development of this autoimmune disease. Zhang et al [71] found that IFI35 hypomethylation in CD3 + T cells can enhance the proliferation of mesangial cells relevant to lupus nephritis by deleting the methylation status of lupus kidneys.…”
Section: Dna Hypomethylation In Sle-cd4 + T Cellsmentioning
confidence: 99%
“…Under these conditions, many sensitive functionalities that cannot survive deprotection and cleavage conditions used in traditional ODN synthesis technologies but can co-exist with ODN can survive, thus, the Dim-Dmoc technology can be used to synthesize sensitive ODNs. We expect that the technology will find applications in many areas including developing new DNA and RNA cross-linking agents for applications such as antisense drug development, disease diagnosis, nucleic acidprotein interaction studies; and synthesizing sensitive model DNA analogs for studies such as DNA methylation and demethylation, and DNA damage and repair (Ali et al, 2006;Bley et al, 2011;Brickner et al, 2019;Calle-Fabregat et al, 2020;Gillingham & Sauter, 2017;Greenberg & Bourc'his, 2019;Michalak et al, 2019;Pande et al, 1999;Rhee & Pugh, 2011;Soll et al, 2017;Urbano et al, 2019).…”
Section: Background Informationmentioning
confidence: 99%
“…The major chromatin changes in immune cells occur by DNA methylation and histone modifications, but also ATP‐dependent chromatin remodelling. The DNA methylation pattern primarily changes during haematopoiesis to alter gene expression patterns, 34 while acetylation and methylation of histones contribute to changes in gene expression also during differentiation and activation of immune cells 35‐37 . The epigenetic modification of chromatin is precisely regulated via histone‐modifying enzymes and chromatin remodelling enzymes acting on specific loci, resulting in specific changes in gene expression, chromatin organization and other DNA regulatory processes.…”
Section: Epigenetic Mechanisms In Immunitymentioning
confidence: 99%